Structure and Electrical Properties of Superionic Ceramics Based on Silver-Enriched (Cu0.25Ag0.75)7SiS5I Solid Solution - Pogodin Artem; Погодін Артем; Shender Iryna; Шендер Ірина; Bereznyuk Serhiy; Сергій Березнюк; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; Кохан Олександр; Suslikov Leonid; et al. (Інститут теоретичної фізики ім. М.М. Боголюбова НАН України, 2021)
Abstract. (Cu0.25Ag0.75)7SiS5I-based superionic ceramics were fabricated by using the micro- and nanopowders. The XRD technique and microstructural analysis are applied for the structural studies of powders and ceramic samples. The impedance measurements of ceramic samples are carried out in the frequency range from 10 Hz to 2 × 106 Hz and temperature interval from 292 K to 383 K. The contributions of ionic and electronic conductivities into the total electrical conductivity are determined, and their temperature dependences are investigated. The influence of the size effect on ionic and electronic conductivities and their activation energies in (Cu0.25Ag0.75)7SiS5I-based ceramics is studied.
Структура та електричнi властивостi суперiонної керамiки на основi збагаченого срiблом твердого розчину (Cu0.25Ag0.75)7SiS5I
Keywords: argyrodite; superionic conductor; ceramic; ionic conductivity; activation energy